VEHICLE STEERING CONTROL DESIGN BASED ON AN INTEGRATED DYNAMIC MODEL WITH ANTI-LOCK BRAKING SYSTEM AND ADAPTIVE AUTOMATIC CONTROL - Wisnujati, Andika; Muzamil, Sanupal (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
This research presents the design and development of a mathematical model for a vehicle steering system guided by the Antilock Braking System (ABS) with integrated automatic control. The purpose of this study is to enhance vehicle stability and steering performance, particularly under critical braking conditions where loss of traction and directional control commonly occur. The proposed model integrates ABS dynamics with an automatic steering control algorithm to simulate real-time responses of the vehicle under various road and driving scenarios. The mathematical formulation is based on vehicle kinematics and dynamics, incorporating nonlinear tire characteristics, braking force distribution, and steering angle adjustments. A control system utilizing PID (Proportional-Integral-Derivative) component is embedded into the model to optimize the coordination between braking and steering operations. Simulation results using MATLAB show that the integrated system significantly improves steering accuracy, reduces stopping distance, and maintains vehicle stability during sudden braking and turning maneuvers. The findings suggest that combining ABS with intelligent steering control contributes to safer driving, especially on slippery or uneven surfaces. This research serves as a foundational step toward the development of more advanced driver-assistance systems (ADAS) and contributes to the ongoing efforts in automotive safety engineering.